2010
DOI: 10.1016/j.tate.2009.02.018
|View full text |Cite
|
Sign up to set email alerts
|

University teacher competencies in a virtual teaching/learning environment: Analysis of a teacher training experience

Abstract: This paper attempts to shed light on the competencies a teacher must have in order to teach in online university environments. We will relate a teacher training experience, which was designed taking into account the methodological criteria established in line with previous theoretical principles. The main objective of our analysis is to identify the achievements and difficulties of a specific formative experience, with the ultimate goal of assessing the suitability of this conceptualmethodological framework fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
1
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(87 citation statements)
references
References 12 publications
7
69
1
10
Order By: Relevance
“…Most online education programs still adopt a traditional homogenous learning model with one single set of learning materials for all learners, though they have different backgrounds, learning styles, and cognitive capabilities. This lack of flexibility in a homogeneous model could be one reason that VLEs supporting those online education programs have not been as successful as expected [5,6,9,23,24,27,29].…”
Section: Virtual Learning Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most online education programs still adopt a traditional homogenous learning model with one single set of learning materials for all learners, though they have different backgrounds, learning styles, and cognitive capabilities. This lack of flexibility in a homogeneous model could be one reason that VLEs supporting those online education programs have not been as successful as expected [5,6,9,23,24,27,29].…”
Section: Virtual Learning Environmentsmentioning
confidence: 99%
“…This instrument was developed by Green and Taber. 5 Learning Performance was measured by two constructs, Perceived learning Performance and Actual Learning Performance were measured by the final examination score.…”
Section: Measurementsmentioning
confidence: 99%
“…In the e-learning environment, the social role of tutors has been highlighted as a component of emotional support (González-Sanmamed, Muñoz-Carril, & Sangrà, 2014;Baran, Correia, & Thompson, 2011;Guasch et al, 2010), which was suggested to affect the learning process and outcomes. The social role is identified by Berge (1995) as one of four necessary roles assumed by instructors in CMC situations and is ranked fourth in terms of the priority of eight roles associated with online instructors in Bawane and Spector's (2009) study.…”
Section: The Priorities Of Tutor Roles and Competencies Compared Withmentioning
confidence: 99%
“…Teacher culture is a sub culture of the school culture, which is the formation of teachers in teaching activities and values and behavior development mainly include teachers' occupation consciousness, role identity, education concept, value orientation, emotional and behavioral reactions [5] [6].Local colleges and universities should gradually change the concept of management, with the "soft control" of teachers' culture to balance the "high voltage centralization" under the rigid institutional environment, so that the management of teachers is more humane. University education is characterized by individuality and creativity, respect for knowledge and respect for talent, only through the development of teachers' subjective initiative.…”
Section: Strengthen the Humanized Managementmentioning
confidence: 99%